Proceedings of the 20th ACM International Conference on Multimodal Interaction 2018
DOI: 10.1145/3242969.3243023
|View full text |Cite
|
Sign up to set email alerts
|

Automated Affect Detection in Deep Brain Stimulation for Obsessive-Compulsive Disorder

Abstract: Automated measurement of affective behavior in psychopathology has been limited primarily to screening and diagnosis. While useful, clinicians more often are concerned with whether patients are improving in response to treatment. Are symptoms abating, is affect becoming more positive, are unanticipated side effects emerging? When treatment includes neural implants, need for objective, repeatable biometrics tied to neurophysiology becomes especially pressing. We used automated face analysis to assess treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…To be consistent with previous work, we selected patch sequences of length T = 20 within that range. The CNN architecture used in this study has been shown to be successful in previous studies (Cohn et al, 2018;Onal Ertugrul et al, 2019a,c). Two differences from previous work may be noted.…”
Section: Networkmentioning
confidence: 69%
“…To be consistent with previous work, we selected patch sequences of length T = 20 within that range. The CNN architecture used in this study has been shown to be successful in previous studies (Cohn et al, 2018;Onal Ertugrul et al, 2019a,c). Two differences from previous work may be noted.…”
Section: Networkmentioning
confidence: 69%
“…We used CNN architecture given in Fig. 1 in our experiments since it has been shown to perform well and provide meaningful results in a cross-domain setting [54]. One of the limitations of our work is, we do not know whether a deeper CNN would perform better.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…To compare AU-specific within-and cross-domain transfer, we use both deep and shallow approaches in two databases that represent different domains. The deep approach is a CNN architecture [54]; the shallow approach is a support vector machine (SVM) with handcrafted features. One database used for training is an expanded version of BP4D+ [6] (which we refer to as EB+).…”
Section: Methodsmentioning
confidence: 99%
“…A study using single-photon emission computed tomography found that nucleus accumbens DBS induced striatal dopamine release in patients with OCD (17). Using AFAR, we have been able to demonstrate that ventral striatum DBS can turn up the gain on positive valence affect (8). For the most part, patients with OCD are driven by harm avoidance (18,19), and their compulsions are aimed at preventing negative outcomes and are not inherently pleasurable, thus differentiating compulsions from behavioral addictions.…”
mentioning
confidence: 84%